The impact of crude glycerol from biodiesel production and its trace element content on biomethane production in a batch experiment - modelling as a step towards impartial routine comparison of results - Kolbl Repinc, Sabina (Acta hydrotechnica, 2021)
In this study, crude glycerol from the biodiesel industry was tested as a co-substrate in biogas production. To investigate the influence of crude glycerol and the underlying trace element (TE) content on the efficiency of biomethane production, a batch experiment using Automatic Methane Potential Test System (AMPTS II) was carried out. The single addition of crude glycerol significantly contributed only to the total content of K (14.4%), Si (17.3%), and P (11.6%), whereas the contributions of other metals were within the range of other substrates. The addition of crude glycerol increased biomethane production, however, its utilization beyond 1% of total volume resulted in prolonged lag phase and final cessation of biomethane production. The negative effects of inorganic salts present in crude glycerol were reflected in progressively diminishing parts of glycerol and methanol being utilized in its anaerobic digestion, posing serious problems for daily routine use. A nonlinear least square regression analysis was performed to fit the Gompertz, Logistic, Transfer, and Richards models to biomethane production. The most suitable model was the Richards model, exhibiting the best fit to the experimental curves for complex substrates. Glycerol fractions remaining after biodiesel production have to be pre-tested for their negative effects on the content of TEs and inorganic salts, lag phase in biogas production, before they are used as co-substrates in biogas production phase.